Creep rupture behavior of a bagasse fiber-polypropylene composite - foroogh dastoorian; Mohammad Layeghi; Ghanbar Ebrahimi; Mehdi Tajvidi; Seid Majid Zabihzadeh (تحقیقات علوم چوب و کاغذ ایران, 2016)
In the present study, creep rupture behavior of a bagasse fiber- polypropylene composite was investigated. Two accumulated damage model (EDRM and Wood) and an energy based failure model (R-W) were adopted to describe the load duration influence on the studied composite. Results have shown that at very high stress levels, the EDRM and Wood models underestimated and overestimated the time to failure than static value respectively. This was attributed to the difference between application of static loading and creep loading. Findings indicated that the all three models were able to describe the creep rupture behavior of the studied composite and among this; the Wood model has shown a better fitting with experimental data, statistically. Based on findings in the present research, it can be concluded that the R-W model was more conservative in predicting time to failure in comparison with the two other models, and the reason can be attributed to the difference between failure criteria in energy based models and accumulated damage models. Results also showed that with increasing stress levels, the secondary stage of creep will shorten and at high stress level, the tertiary stage of creep will be more dominant